Case Report: A Brodie's abscess in the spine in a female patient treated by percutaneous endoscopic debridement and drainage - Yang, Tsung-Lin; Huang, Chen-Pang; Wu, Hung-Kang; Hsu, Yu-Pao; Yu, Ching-Hsiao (Frontiers in Surgery, 2026)
Brodie's abscess is a rare subacute osteomyelitis. It is characterized by a localized, well-demarcated abscess within the bone, typically in the metaphysis of long bones in young male patients. Spine involvement is extremely rare, accounting for only 1% of all cases. Due to the rarity of this condition, there is no established standard treatment. We present a case of a 37-year-old female patient with a Brodie's abscess in her L1–L2 vertebrae who was successfully treated with percutaneous endoscopic debridement and drainage (PEDD) and concomitant percutaneous instrumentation, the necessity of which was underscored by objective stability assessments. The patient's back pain significantly improved after the surgery, and she was able to walk without any support. The patient was discharged on postoperative day 14 and was followed up for 1 year, with no recurrence of the infection. We believe that PEDD is a safe and effective treatment option for a Brodie's abscess in the spine.